The impact of corporate reputation and reputation damaging events on financial performance: Empirical evidence from the literature - Gatzert, Nadine (European management journal, 2015)
Corporate reputation and reputation risk are becoming increasingly relevant for firms, also caused by its relevance for firm value. In this context, this paper provides a comprehensive survey of empirical evidence in the literature regarding the relation between reputation damaging events, corporate reputation, and corporate financial performance, thereby also taking into account stakeholder behavior. The review is also intended to determine to what extent the current literature allows a holistic understanding of these relationships in the sense of the causal chain of events, which is of high relevance when managing reputation and reputation risk. Thus, focus is first laid on empirical evidence regarding the impact of corporate reputation on stakeholder behavior and on financial performance. Next, the event study literature regarding the effect of reputation damaging events on corporate reputation and financial performance is reviewed, and, finally, implications for risk management are discussed along with the need for future research.